Aortic valve area calculation using 3D transesophageal echocardiography: Implications for aortic stenosis severity grading. Issue 12 (7th October 2020) - Beneduce, Alessandro; Capogrosso, Cristina; Moroni, Francesco; Ancona, Francesco; Falasconi, Giulio; Pannone, Luigi; Stella, Stefano; Ingallina, Giacomo; Melillo, Francesco; Ancona, Marco Bruno; Romano RT, Vittorio; Palmisano, Anna; et al.
Abstract: Aims: Aortic stenosis (AS) grading by 2D‐transthoracic echocardiography (2D‐TTE) aortic valve area (AVA) calculation is limited by left ventricular outflow tract (LVOT) area underestimation. The combination of Doppler parameters with 3D LVOT area obtained by multidetector computed tomography (MDCT) can improve AS grading, reconciling discordant 2D‐TTE findings. This study aimed to systematically evaluate the role of 3D‐transesophageal echocardiography (3D‐TEE) in AS grading using MDCT as reference standard. Methods and results: 288 patients (81 ± 6.3 years, 52.4% female) with symptomatic AS underwent 2D‐TTE, 3D‐TEE, and MDCT for transcatheter aortic valve implantation. Doppler parameters were combined with 3D LVOT areas measured by manual and semi‐automated software 3D‐TEE and by MDCT to calculate AVA, reassessing AS severity. Both 3D‐TEE modalities demonstrated good correlation with MDCT, with excellent intra‐observer and inter‐observer variability. Compared to MDCT, 3D‐TEE measurements significantly underestimated AVA ( P ANOVA  < .0001), although the difference was clinically acceptable. Compared to 2D‐TTE, 3D‐TEE manual and semi‐automated software reclassified severe AS in 21.9% and 25.2% of cases, respectively ( P  < .0001), overcame grading parameters discordance in more than 40% of cases in patients with low‐gradient AS ( P  < .0001) and reduced the proportion of low‐flow states in nearly 75% of cases when combined to stroke volume index assessment ( P  < .0001). 3D‐TEE imaging modalities showed a reduction in the proportion of patients with low‐gradient and pathological AVA as defined by 2D‐TTE, and improved AVA and mean pressure gradient agreement with current guidelines cutoff values. Conclusion: 3D‐TEE AVA calculation is a reliable tool for AS grading with excellent reproducibility and good correlation with MDCT measurements. Abstract : AS grading using 3D‐TEE combined approach.